Detection of antibodies of the IgM class in sera of patients recently infected with influenza viruses. Issue 5 (May 1976) - Buchner, Y I; Heath, R B; Collins, J V; Pattison, J R
Abstract : Sucrose density gradient ultracentrifugation can be used to detect specific 19S antibodies of the IgM class in the sera of patients recently infected with influenza A virus, provided steps are taken to remove non-specific inhibitors of haemagglutination. The usefulness of the procedure for the diagnosis of influenza requires further evaluation.